Notification Mechanisms by Initiative of E-mail Receiver in Systems Based on E-mail/SMS Technologies - Mkhitaryan, Andranik E.; Petrosyan, Arthur S.; Nanassian, Aram S. (Mathematical Problems of Computer Science, 2021)
The feature of mechanisms for the exchange of messages in computer and cellular networks is considered, in order to send a notification to the receiver of e-mail on his/her own initiative using IP and GSM technologies. The peculiarities of technical models for designing a separated system are compared.